Official matches and training sessions: physiological demands of elite junior badminton players - Karen Christie Gomes Sales; Marcos Antônio Pereira Santos; Fabio Yuzo Nakamura; Valmir Oliveira Silvino; Alyson Felipe da Costa Sena; Sérgio Luís Galan Ribeiro; Jefferson Fernando Coelho Rodrigues Júnior; Christian Emmanuel Torres Cabido; Thiago Teixeira Mendes (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: To evaluate the intensity of training and official badminton matches (international championship) in junior elite players. Methods: Twelve elite players from the Brazilian junior national team (6 male and 6 female) were monitored during 19 training sessions and 50 official men's and women's single and double matches in the XXVII Pan-American Junior Games. Subjects underwent an incremental running step test to determine maximal oxygen uptake (VO2max), and an individual relationship between heart rate (HR) and VO2max was established to estimate exercise intensity and oxygen uptake at official matches (OMs) and training sessions. HR was monitored during multi-shuttlecock (MS), technical-tactical (TT), and physical (PS) training methods, as well as during simulated matches (SMs) and OMs. Variables such as %HRmax, HR zones, %VO2max, and energy expenditure were also calculated. Results: OM was the most intense activity monitored for male and female athletes, followed by SM according to %HRmax (86.8 ± 4.1% and 84.4 ± 5.0% for female and male, respectively, in OM vs. 74.6 ± 2.3% and 75.0 ± 5.0% for female and male, respectively, in SM). OM mean energy expenditure was 10.7 ± 0.5 kcal.min-1 for females and 14.9 ± 4.6 kcal.min−1 for males. Conclusion: MS training has less physiological demand and OM presented higher intensity. SM, on the other hand, had the closest physiological demand to an OM.